ZTE Grand S3 to feature eye-based biometrics from EyeVerify. (March 2015) - Unknown
Abstract : Global mobile device maker ZTE has announced its ZTE Grand S3 will have eye-based biometrics from EyeVerify. The solution, Eyeprint ID, will give users a password-free method of unlocking the Grand S3. The solution works by imaging unique vein patterns in the human eye using the Grand S3's front facing camera.